Mycotic Infections in Free-Ranging Harbor Porpoises (Phocoena phocoena) - Kapetanou, Athanasia; IJsseldijk, Lonneke L.; Willems, Dorien S.; Broens, Els M.; Everaarts, Eligius; Buil, Jochem B.; Verweij, Paul E.; Kik, Marja J. L.; Gröne, Andrea (Frontiers in Marine Science, 2020)
Studies on the occurrence of fungal communities in the marine environment are still scarce, but mycotic infections in cetaceans are increasingly reported. Fungal disease following infection with Aspergillus species is most frequently reported, with the respiratory tract commonly affected in cetaceans and other taxa, like humans and birds. Infection with Aspergillus spp. is dependent on the characteristics of the fungus as well as the hosts immune status, with dissemination into other organs being relatively common. Along the southern North Sea, harbor porpoise (Phocoena phocoena) strandings increased significantly since 2005 and necropsies to determine causes of death have been conducted since 2008. Here we describe the post-mortem findings in stranded, free-ranging harbor porpoises on the Dutch coast which were diagnosed with fungal disease, to determine the prevalence of mycotic infections, and to compare them to those described in other species. A total of 18/754 (2.4%) harbor porpoises showed lesions compatible with localized or disseminated fungal disease as confirmed by histological examination. The respiratory tract was most commonly affected (67%), followed by the central nervous system (CNS, 35%) and auditory system (AS, 18%). Aspergillosis was confirmed for 11/18, by fungal growth (as A. fumigatus species complex, n=9) and PCR (as Aspergillus spp., n=1, and as A. fumigatus sensu strictu by sequence analysis, n=1). One live stranded and euthanized animal presented partial hemiplegia of the blowhole and therefore an MRI was conducted, which resulted in a unique image of the extensive, fungus-induced lesion in the left cerebellar hemisphere, deforming and displacing the brainstem, and additionally affected the AS. The gross- and histologic lesions in the 18 porpoises diagnosed with fungal disease were similar to changes described in other mammalian species. The prevalence of fungal disease in free-living harbor porpoises is lower than seen in captive and rehabilitated animals, suggesting that captivity increases the risk to develop mycotic infections. Finally, fungal infection in the CNS and AS are usually considered consequences of vascular dissemination originating from pulmonary foci. However, only 1/7 cases with otitis and/or encephalitis demonstrated pulmonary aspergillosis, suggesting a different pathogenesis.